SISTEM PAKAR DIAGNOSIS PERUBAHAN CUACA BERBASIS ANDROID - wen, Herman; Rizki, Sestri Novia (Computer Science and Industrial Engineering, 2021)
Weather is part of carrying out an activity and affects several fields, such as determining crops in agriculture and aviation on departure in an airplane. Android is an operating system that can be used and is open source code, android can develop and modify easily. The Meteorogy, Climatology and Geophysics Agency (BMKG) is tasked with monitoring the weather that predicts the weather using two methods, namely conventional methods and statistical methods which can cover a radius of 5-10 km on land and 50 km at sea for observations in a predicted area. The problem in this study is that the weather diagnosis requires a complex database, so a method for accurate weather diagnosis is needed and weather diagnosis information is very difficult to obtain. Forward chaining is a technique that starts the search for data and facts, and the data is used as a conclusion to become a solution. So the forward chaining method can help make diagnoses related to the weather. The purpose of diagnosing weather changes is to be able to help the special community in the Riau Islands to help plan activities. Researchers are designed to be able to assist the surrounding community in obtaining weather diagnosis information by providing complete information and accurate results but carried out efficiently. Keywords: Weather, Android, Forward Chaining, BMKG